KONTRADIKSI, AMBIGUITAS, DAN NONSENSE DALAM KUMPULAN PUISI NYANYIAN KAKI LANGIT KARYA DASRI AL MUBARY - Al Husein, M. Arif; Rahman, Elmustian; Rumadi, Hadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract This Research study about how contradiction aspect form, ambiguitas, and nonsen in Hymn Horizon masterpiece anthology of Dasri Al Mubary. This Research use approach qualitative and descriptive method with aim to for the mendeskripsikan of aspects of deviation of meaning covering aspect of kontaradiksi, ambiguitas, and nonsense. source of data of this research that is Horizon masterpiece hymn anthology of Dasri Al Mubary. Data obtained by using data collecting technique, [is] later;then classified pursuant to contradiction aspect category, ambiguitas, and nonsense. As for aspect which implied in study expression ketidaklangsungan deviation of meaning namely contradiction, ambiguitas, and formulated nonsense become node. Pursuant to data analysis, obtained [by] aspect of kontradisi counted 7 poem data, later;then data covering aspect of ambiguitas counted 19 poem data, and data covering aspect of nonsen counted 13 poem data.Keyword : Contradiction, Ambiguitas, Nonsense, Hymn Horizon